A comparative analysis of computer-aided design team performance with collaboration software. Issue 4 (4th July 2018) - Eves, Keenan; Salmon, John; Olsen, Jacob; Fagergren, Fred
ABSTRACT: For the past several years, the BYU CAD Lab has been developing collaborative computer-aided design (CAD) software. As this software is being developed, industry seeks to better understand the differences in performance between teams using multi-user CAD and single-user CAD to make informed decisions about implementing this new software into their engineering processes. In order to better understand the differences in performance between teams, an experimental study was conducted in which four multi-user teams and four single-user teams competed to create the best model of a hand drill. Key findings of this study were that multi-user CAD increases awareness of teammates' activities as well as communication between team members. Performance, with respect to the metrics of quality and time for completion, could be improved with increased familiarity with the multi-user CAD software. Future research directions are suggested and discussed. GRAPHICAL ABSTRACT: